Atraumatic Restorative Treatments in Australian Aboriginal Communities: A Cluster-randomized Trial. (October 2021) - Arrow, P.; Piggott, S.; Carter, S.; McPhee, R.; Atkinson, D.; Mackean, T.; Kularatna, S.; Tonmukayakul, U.; Brennan, D.; Nanda, S.; Palmer, D.; Jamieson, L.
Introduction: The management of early childhood caries (ECC) is challenging. Objectives: A model of care based on Atraumatic Restorative Treatment and the Hall Technique (ART-HT) to manage ECC was evaluated among remote Aboriginal communities in Australia. Methods: Aboriginal communities in the North-West of Western Australia were invited to participate and consenting communities were randomized into early or delayed intervention for the management of ECC. Children were examined at baseline and at the 11-mo follow-up. The early intervention group (test) was provided with the ART-based dental care at baseline while the delayed intervention group (control) was advised to seek care through the usual care options available within the community. At follow-up, both groups were examined by calibrated examiners, and were offered care using the ART-HT approach. Changes from baseline to follow-up in caries experience were tested using paired tests. Multivariate analysis after multiple imputation of missing data used generalised estimating equation (GEE) controlling for clustering within communities. Results: A total of 25 communities and 338 children (mean age = 3.6 y, SD 1.7) participated in the study (test = 177). At follow-up, 231 children were examined (68% retention, test = 125). At follow-up, children in the test group had more filled teeth (test filled teeth = 1.2, control filled teeth = 0.2, P < 0.001) and decreased levels of decayed teeth (mean test = 0.7 fewer teeth with decay, mean control = 1.0 more tooth with decay, P < 0.001). GEE analysis controlled for baseline caries experience, age, sex, and community water fluoride levels found increased rates of untreated decayed teeth (RR = 1.4, P = 0.02) and decreased rates of filled teeth (RR = 0.2, P < 0.001) at follow-up among the control group. Conclusion: A model of care relying on the principles of minimally invasive atraumatic approaches enabled the delivery of effective dental services to young children (<6 y) in remote Aboriginal Australian communities resulting in increased levels of care and improved oral health. Knowledge Transfer Statement: This cluster-randomized trial tested a multi-component model of dental care to young children with ECC in remote Aboriginal communities in Australia. The intervention, based on the atraumatic approaches using minimally invasive techniques encompassing preventive care, Atraumatic Restorative Treatment and the Hall Technique (ART-HT), delivered more restorative care and reduced the incidence of caries. This model of care was more effective than available standard care and should be incorporated into mainstream service delivery programs.